To buy or not to buy? The effect of time scarcity and travel experience on tourists' impulse buying. (January 2021) - Li, Chunxiao; Wang, Yuting; Lv, Xingyang; Li, Hui
Abstract: By its very nature, tourism is a temporary experience. But how time scarcity makes an impact on tourists' impulse buying is still unclear. By looking into the role played by travel experience and overconfidence, this study explores the mechanism behind the influence of time scarcity on tourist impulse buying of local products through an integrated series of experiments together with a post-trip survey. The results show that the interaction between time scarcity and travel experience affects impulse buying. For tourists with rich travel experience, time scarcity increases their impulse buying, while for tourists with less travel experience, time scarcity decreases it. Overconfidence plays a mediating role in the effect of time scarcity and travel experience on tourists' impulse buying. Highlights: Travel experience moderates the impact of time scarcity on impulse buying. For tourists with more travel experience, time scarcity increases impulse buying. For tourists with less travel experience, time scarcity decreases impulse buying. Overconfidence mediates the interaction of time scarcity and travel experience. This research integrates laboratory experiments and post-trip survey.